The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su142315488
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Thermal-Oxidative Molecular Degradation of Polystyrene and Acrylonitrile Butadiene Styrene during 3D Printing Starting from Filaments and Pellets

Abstract: An important polymer processing technique is additive manufacturing (AM), which enables shape-free design of complex final parts with limited waste during the development change, at least if the impact of molecular degradation reactions is minimized. In the present work, polystyrene (PS) and acrylonitrile butadiene styrene (ABS) polymer have been processed via: (i) fused filament fabrication (FFF), separately accounting for the prior single screw extrusion (SSE) filament production; and (ii) pellet-based addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…The thermal degradation of ABS in the neat ABS filament took place in two temperature ranges at 300–480 and 480–580 °C with a residual weight of about 0.65% at 700 °C (Table S1 in the Supporting Information). It was previously reported that the decomposition of butadiene, styrene, and acrylonitrile units of ABS began at 340, 350, and 400 °C, respectively . TPU in the neat TPU filament also degraded in two temperature ranges at 295–480 and 480–650 °C with a residual weight of approximately 0.80% at 700 °C.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The thermal degradation of ABS in the neat ABS filament took place in two temperature ranges at 300–480 and 480–580 °C with a residual weight of about 0.65% at 700 °C (Table S1 in the Supporting Information). It was previously reported that the decomposition of butadiene, styrene, and acrylonitrile units of ABS began at 340, 350, and 400 °C, respectively . TPU in the neat TPU filament also degraded in two temperature ranges at 295–480 and 480–650 °C with a residual weight of approximately 0.80% at 700 °C.…”
Section: Resultsmentioning
confidence: 86%
“…It was previously reported that the decomposition of butadiene, styrene, and acrylonitrile units of ABS began at 340, 350, and 400 °C, respectively. 28 TPU in the neat TPU filament also degraded in two temperature ranges at 295–480 and 480–650 °C with a residual weight of approximately 0.80% at 700 °C. The first decomposition stage was associated with the scission of the urethane linkage of TPU hard segment, while the latter decomposition stage involved the degradation of the polyol chain of TPU soft segment.…”
Section: Resultsmentioning
confidence: 99%
“…No significant differences regarding degradation were found for PLA processed via both techniques. In a follow-up study, the effects of printing parameters and technique on the degradation and macroscopic properties have been studied for PS and ABS [7]. The FFF process generated for ABS more fission (scission), as the mechanical loading in the filament production step is high, whereas in the PBAM process more crosslinking was evident, thus a higher thermal loading took place.…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…In general, multiple-step processing techniques are more prone to induce polymer degradation, a more recent example being additive manufacturing (AM) or 3D printing via fused filament fabrication (FFF). This AM technique first requires the filament fabrication via conventional extrusion and then the actual 3D printing, leading to a higher level of polymer degradation than single-step 3D printing [7][8][9]. AM is defined by ISO/ASTM as a process of joining materials to make parts from 3D model data, usually layer by layer [10].…”
Section: Introductionmentioning
confidence: 99%
“…Among different types of FDM filament materials commercially available in the market, the acrylonitrile butadiene styrene (ABS) thermoplastic is a crucial material in engineering applications due to its good response to mechanical properties (Ozsoy et al , 2021; Dudek, 2013a; Ceretti et al , 2022). ABS, being an oil-based thermoplastic copolymer, has a great balance of properties, such as heat resistance, impact strength and rigidity.…”
Section: Introductionmentioning
confidence: 99%